2019
DOI: 10.37148/arteri.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Uji Skrining Fitokimia Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea Batatas L)

Abstract: Purple sweet potato is a very familiar plant for us, and the most common is white sweet potato, purple, yellow ororange. The advantages of colored purple sweet potatoes contain anthocyanins. Anthocyanins are a secondarymetabolite of flavonoids and polyphenols that can act as antioxidants. This concentration of anthocyanins is whatcauses some kind of purple potato to have a gradient of different shades of purple. Anthocyanins provide excellenthealth effects namely as antioxidants and anticancer due to electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…The phytochemical test results showed that qualitatively sweet potato leaf extract contained secondary metabolites in the form of flavonoids, alkaloids, saponins, tannins, and triterpenoids (Figure 1). This was in accordance with the results of research that sweet potato leaves contained alkaloids, flavonoids, tannins, and saponins compounds (Susanto et al, 2019;Lalu et al, 2017). With the presence of these secondary metabolite compounds, sweet potato leaf extract has the potential as an antibacterial natural ingredient.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The phytochemical test results showed that qualitatively sweet potato leaf extract contained secondary metabolites in the form of flavonoids, alkaloids, saponins, tannins, and triterpenoids (Figure 1). This was in accordance with the results of research that sweet potato leaves contained alkaloids, flavonoids, tannins, and saponins compounds (Susanto et al, 2019;Lalu et al, 2017). With the presence of these secondary metabolite compounds, sweet potato leaf extract has the potential as an antibacterial natural ingredient.…”
Section: Resultssupporting
confidence: 92%
“…Sweet potato leaves are one part of the plants that are spread evenly throughout Indonesia which is usually used as vegetables. This leaves have health benefits because they contain secondary metabolite compounds such as flavonoids, alkaloids, tannis, and saponins (Susanto et al, 2019). With the presence of these active compounds, these leaves have antibacterial activity against various bacteria, one of which is Staphylococcus aureus (Rangotwat et al, 2016;Osuntokun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Obat tradisional adalah obat yang tidak menimbulkan banyak efek samping karena kandungan kimianya masih bisa dicerna oleh tubuh untuk dikonsumsi (Susanto, Rahmawati, Farmasi, Medica, & Husada, 2019). Selain sangat bermanfaat obat tradisional lebih mudah terjangkau masyarakat dan ketersediaannya tidak terbatas (Purwokanti, 2021).…”
Section: Pendahuluanunclassified
“…Purple sweet potato is a type of sweet potato that is often found in Indonesia apart from the white, yellow and red ones (Batubara et al, 2023;Pratiwi et al, 2023;Susanto et al, 2019). The purple sweet potato type Ipomoea batatas L. Poir has a fairly deep purple color in the flesh of the sweet potato, so it attracts a lot of attention.…”
Section: A Introductionmentioning
confidence: 99%